Digital skills readiness of selected western Balkan Countries - Majovski, Irina; Janevski, Zoran; Petkovski, Vladimir (Economic Development, Journal of the Institute of Economics – Skopje, 2018)
The latest technological developments have subsequently impacted businesses imposing changes to the methods of production and the patterns of employment. Businesses are becoming heavily depended on new technologies and strive to invest in latest technology so as to leverage it in increasing productivity and innovation. To capitalize on the opportunities that have been created with the high-tech solutions, businesses require digitally skilled workers who can use advanced technology in daily business operations. Since advance technology has dispersed across many industries and occupations, the demand for digital skills has dramatically increased in most sectors of the economy. Many emerging jobs involve work activities that require a complementary skillset of advanced digital skills, problem-solving and technical skills, and entrepreneurial or business skills. Developing the required skills for the digital age in the region leaves much to be desired. The curricula in education institutions should be revised, modern teaching methods should be introduced and critical thinking, creativity and problem solving should be encouraged among students. Using a set of digital tools in formal education as an integral part of the learning process will foster digital skills excellence among future workers.
Keywords: Keywords: digital economy, digital skills, human resources, ICT development